The Influence of Leadership Style and Knowledge Sharing on Employee Performance at the Mamuju Regency Transportation Service Office - Nur Indah Rukmana; Suwanti; Roshita Amalyah Rasyid (Economos : Jurnal Ekonomi dan Bisnis, 2025)
This study examines the influence of leadership style and knowledge sharing on employee performance at the Mamuju Regency Transportation Service Office. Employee performance in public organizations plays a strategic role in ensuring service quality, yet initial observations indicated issues related to coordination, discipline, and task implementation. Using a quantitative approach, data were collected through questionnaires distributed to all 38 civil servants using a saturated sampling technique. Data analysis employed validity and reliability testing, multiple linear regression, and hypothesis testing using t-tests and F-tests. The results reveal that leadership style partially has no positive and significant effect on employee performance, indicating that existing leadership behaviour has not optimally contributed to improving individual performance. Conversely, knowledge sharing shows a positive and significant effect on employee performance, demonstrating the critical role of knowledge exchange in enhancing work quality and problem-solving capacity. Simultaneously, leadership style and knowledge sharing significantly influence employee performance, implying that these variables collectively contribute to organizational effectiveness. These findings support prior research highlighting the importance of knowledge sharing in public sector performance, yet differ from studies that emphasize leadership as a primary determinant. The study provides theoretical implications for strengthening human resource management in government institutions and practical recommendations for improving collaborative work culture and knowledge dissemination.